PERAN EDUKASI HUKUM DALAM PERLINDUNGAN HAK ANAK DI SEKOLAH TERHADAP KASUS BULLYING DI SEKOLAH: SOSIALISASI DI MA DARUL IRFAN KOTA SERANG - Fitri Agus Rukson; Yaqin Qobul; Sandrifan Pahlevi; Mohamad Dzidni Dzakwan; Wulan Sari Saputri (Jurnal Riset Multidisiplin Edukasi, 2026)
Bullying in schools remains a serious issue that can negatively affect children's psychological, social, and academic development. This community service activity aimed to improve students’ understanding of legal education related to the protection of children's rights and bullying prevention at MA Darul Irfan, Serang City. The activity was carried out through legal counseling, discussions, and interactive sessions. The results showed an increase in students’ awareness regarding the forms, impacts, and legal consequences of bullying. Legal education is expected to build students’ awareness and create a safer, more child-friendly school environment.